Unconventional monetary policies at the effective lower bound - Rafael Gerke; Daniel Kienzler; Alexander Scheer (Deutsche Bundesbank, 2021)
This paper presents selected results from a model-based assessment of the impact of unconventional monetary policies. The model is estimated on euro area data and features two types of agents, a financial sector, several real and nominal frictions as well as rational expectations. In our model simulations, we allow for multiple nonlinearities: an occasionally binding effective lower bound (ELB) on the short-term policy rate; a state-dependent and calender-based interest rate forward guidance; state-dependent asset purchases conducted only at the ELB. There are four main results. First, state-dependent forward guidance can reduce the volatility of the economy in comparison to unconditional calendar-based forward guidance. Second, the ELB induces a large negative in ation bias if the central bank has only its short-term policy rate at its disposal. Third, asset purchases that are initiated only at the ELB can provide significant in ation stabilisation, but it remains uncertain whether they allow the distortions created by the ELB to be fully off- set. This is the case, for instance, when an upper limit on purchases is imposed. Fourth, an appropriate reinvestment strategy might help to mitigate the limits of asset purchases.
Keywords: D78; E31; E43; E44; E52; E58; 330; Effective lower bound; forward guidance; state-dependent asset purchases; reinvestment; make-up strategies; Bayesian estimation